The Urgency of Stakeholder Cyberspace Collaboration to Support Indonesia’s National Defense - Firdini, Firdini; Gultom, Rudy Agus Gemilang; Widodo, Pujo; Jupriyanto, Jupriyanto (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
In today's interconnected digital world, stakeholder collaboration in cyberspace is crucial for national defense. Advances in information and communication technology have transformed daily life but also introduced complex cyber threats like cyber warfare, cybercrimes, and cyber terrorism, challenging security and stability. The objective of this study is to emphasize the importance of collaboration among diverse stakeholders in enhancing national defense against cyber threats. The methodology involves analyzing existing literature and case studies to understand the impact of collaboration on cybersecurity maturity and national defense strategies. The research findings, derived from SWOT and PESTLE analyses, have highlighted the strengths and weaknesses in collaboration, underscoring the significance of leveraging strengths and addressing weaknesses to establish a robust defense framework. To enhance national defense against cyber threats, a holistic approach is essential, combining political collaboration, economic partnerships, social awareness programs, technological advancements, legal harmonization, and environmental resilience strategies. Key recommendations include fostering regular communication among stakeholders, pooling resources for cybersecurity investments, promoting cybersecurity education, integrating advanced technologies like AI and IoT security solutions, and aligning legal frameworks across jurisdictions.